Biocatalytic Synthesis of D-Allulose Using Novel D-Tagatose 3-Epimerase From Christensenella minuta - Wang, Yang; Ravikumar, Yuvaraj; Zhang, Guoyan; Yun, Junhua; Zhang, Yufei; Parvez, Amreesh; Qi, Xianghui; Sun, Wenjing (Frontiers in Chemistry, 2020)
D-allulose, which is one of the important rare sugars, has gained significant attention in the food and pharmaceutical industries as a potential alternative to sucrose and fructose. Enzymes belonging to the D-tagatose 3-epimerase (DTEase) family can reversibly catalyze the epimerization of D-fructose at the C3 position and convert it into D-allulose by a good number of naturally occurring microorganisms. However, microbial synthesis of D-allulose is still at its immature stage in the industrial arena, mostly due to the preference of slightly acidic conditions for Izumoring reactions. Discovery of novel DTEase that works at acidic conditions is highly preferred for industrial applications. In this study, a novel DTEase, DTE-CM, capable of catalyzing D-fructose into D-allulose was applications. In this study, a novel DTEase, DTE-CM, capable of catalyzing D-fructose into D-allulose was DTE-CM on D-fructose was found to be remarkably influenced and modulated by the type of metal ions (co-factors). The DTE-CM on D-fructose was found to be remarkably influenced and modulated by the type of metal ions (co-factors). The 50°C from 0.5 to 3.5 h at a concentration of 0.1 mM. The enzyme exhibited its maximum catalytic activity on D-fructose at pH 6.0 and 50°C from 0.5 to 3.5 h at a concentration of 0.1 mM. The enzyme exhibited its maximum catalytic activity on -fructose at pH 6.0 and 50°C with a Kcat/Km value of 45 mM−1min−1. The 500 g/L D-fructose, which corresponded to 30% conversion rate. With these interesting catalytic properties, this enzyme could be a promising candidate for industrial biocatalytic applications.